Impact of public road investment on poverty alleviation in rural Laos - Inthakesone, B.; Kim, T. (International Journal of Applied Business and Economic Research, 2016)
Rural roads have been widely known as champion for poverty alleviation instruments. Connecting to roads provides market access opportunities, develop market linkage, and improve farm production through technology improvement. This circulation ensures a stable income; later improve living standard and then poverty reduction. In Laos, road networks are extremely poor, many districts lack roads linked to the main national transportation. The paper will find out the mechanism of how the rural roads could contribute to the improvement of household livelihood, and standard of living. Difference in Differences (DD) method will be used in this analysis. The results confirm that the villages with road access may increase their total income around 14.9% compared to the ones without road access, and the result consistent with previous study as well. The recommendation for government to curve the poverty in Laos is to incorporate the connecting rural road plan into the national development strategy to allow the rural communities to have easy access to the main infrastructure and to be mainstreamed into the country economy to improve their daily activities and their livelihood.